Dating loom weights from Százhalombatta-Földva´r, Hungary - Bergerbrant, Sophie; Vicze, Magdolna (Archaeological Textiles Review, 2020)
Loom weights are difficult to date as they are fairly consistent in weight and shape over long periods. This article discusses the dating of 194 light loom weights with no contextual data from Száhalombatta, Hungary. The aim of this paper is to present previously unpublished material and identify the period to which the textile tools belong. It shows that the light loom weights in this study most likely belong to the Hallstatt period based on the find site's characteristics and comparison with loom weights from dated contexts.